Genomic data from Humboldt penguin ( Spheniscus humboldti ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The Humboldt penguin inhabits coastal Chile and Peru. They nest on islands and rocky coasts, holes in guano and in caves. Humboldt penguin populations are declining, and the International Union for Conservation of Nature (IUCN) classifies them as vulnerable. We sequenced the genome of an adult Humboldt penguin from Copenhagen Zoo, of Peru and Chile lineage (provided by Mads Bertelsen) to a depth of approximately 172x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled scaffolds of high quality sequences total 1.21Gb, with the contig and scaffold N50 values of 19.38Kb and 5.94Mb respectively. We identified 16587 protein-coding genes. ...